Pemanfaatan Termoelektrik Sebagai Sumber Energi Terbarukan - Mohamad Diki; Charis Fathul Hadi; Risk Fita Lestari; Rezki Nalandari (Prodi Teknik Elektro Universitas PGRI Banyuwangi, 2022)
Abstract - Research has been carried out on power generators using thermoelectric or Peltier elements, with the aim of knowing how much output or output voltage the module produces by varying the temperature entered into the Peltier module. Peltier element is a material that can convert a certain temperature difference into electrical energy using the principle of the Seebeck effect. In this research, a thermoelectric generator module is designed using a Peltier element type SP184827145SA. This study aims to determine the characteristics of the power generated by the thermoelectric generator module with a series of Peltier elements with a given temperature variation, the voltage generated by the thermoelectric element is proportional to the temperature given on the high temperature side, the higher the temperature given, the greater the voltage. which are issued. From the research, it was found that when the Peltier heat temperature reaches 70ᵒc it can produce an output of 1.49v, while when the temperature gets lower the lower the voltage generated